Perceptions of and Reflections on Aesthetic Education Training from the Perspective of Taiwanese Preschool Educators - Liza Lee; Pei-Ju Chao (MDPI AG, 2023)
Many studies have demonstrated that music has many benefits for children's physical and mental development. However, many preschool educators have scant preparation for or a lack of experience in aesthetic education. The purpose of this study is to explore preschool educators' perceptions of and reflections on aesthetic education training. We conducted a survey associated with three aspects: "aesthetics appreciation", "aesthetics implementation", and "aesthetics evaluation". The results of the study show the majority of participants agreed that (1) musical participation would strengthen participants' attitudes toward aesthetic appreciation through proper aesthetic training programs and (2) musical engagement would benefit young children by enhancing their aesthetic experiences. The attitudes toward aesthetic implementation for young children were more favorable among the middle-aged and experienced participants; (3) musical activities are also a good way to improve young children's aesthetic abilities, which helps to create an aesthetic atmosphere in educational practice. These results indicate that it is vital for preschool educators to receive the appropriate training in aesthetics and continuous assessment to provide high-quality early education to young children.